THE INFLUENCE OF TALENT MANAGEMENT ON WORKFORCE AGILITY MEDIATED BY JOB SATISFACTION - Yulian, Hafizu Dwi; Ekhsan, Muhamad (Dynamic Management Journal, 2023)
With the increasing number of companies in the current era of globalization, an organization is required to be able to improve company performance by maximizing new knowledge and honing talents in its workforce. Talent Management will have an impact on the success of an institution or organization. Lack of ability to read opportunities, develop skills, and lack of the right steps to develop a strategy within an organization will also have a negative impact on the sustainability of an institution. The purpose of this research is to find out whether there is an influence of talent management variables on workforce agility which is mediated by job satisfaction. This research was conducted to examine the effect of talent management on workforce agility mediated by job satisfaction in private elementary schools in Cikampek District. This research uses quantitative methods. Data retrieval is done by distributing questionnaires to respondents. The population in this study were 102 educators from 8 private schools with a sample of 81 respondents. The analytical method used is the SmartPLS 3.0 method. Based on the results of the findings of this study, it helps Teachers to utilize their talents or even increase the potential of each individual's qualified talent while at the same time helping Teachers to continue to maintain their work agility strategy in order to get work results that can give satisfaction to Teachers.